Pelatihan Penerapan Protokol Kesehatan Karyawan Hotel di Masa Tatanan Normal Baru - Fajri, Devy Dwi (Jurnal ABDIMAS PARIWISATA, 2020)
The Training on Implementing Health Protocol of Hotel’s Employees in New Normal Era The pandemic of Corona Virus Disease 2019 (Covid-19) causes the decline of hospitality sector in Yogyakarta Special Region. All hotels’ occupancy level significantly decreases due to the number of tourist visit that is falling. This circumstance results to the temporary closure for almost all of the hotels. The closure causes the hotel employees’ laid off until an undetermined time and the deceleration of regional economic growth. However, the expectation to revive hospitality sector appears while entering the new normal era. The hotels that were previously shut down because of the inability to cover the operational cost are now able to re-operate with the requirement of being capable to apply health protocol for preventing and controlling Covid-19 in accordance to government standard. Therefore, hotel industry players, especially the employees, are necessary to get the training on implementing health protocol in hotel environment. It aims to meet the guests’ needs of clean, healthy, safe and environmental friendly excellent product and service. Thus, the guests’ trust can be regained and hotel sectors’ activities are able to be run well